Design and analysis of stepped reconfigurable rectangular patch antenna for LTE, vehicular and ultra wideband applications - Ajay Babu, M; T P Madhav, B; Bhargavi, G; Sai Krishna, V; Hemanth Kumar Reddy, Y; V.S. Kalyan, G; Venkateswara Rao, M (International Journal of Engineering and Technology, 2017)
A stepped rectangular patch antenna having partial ground loaded with parasitic element is analyzed in this article. The Proposed antenna is connected to a diode on the flip side of the structure that is in between the parasitic element and the partial ground, the two cases ON, OFF are studied and analyzed. In OFF case the antenna got rejected at 3 bands (2 to 2.3 GHz, 2.6 to 3 GHz and 5.8 to 7.9 GHz). On the other hand, in ON case antenna got rejected at single band (3.6 to 4.4 GHz). The maximum gain of 5.5 dB is observed at 7.8 GHz frequency in ON case and the maximum gain of 4.4 dB is observed at 9 GHz frequency in OFF case with an average gain of 3.3dB in ON case and 2.9dB in OFF case. The proposed antenna works in almost at all ultra wideband applications having single rejection at 3.6GHz-4GHZ.The proposed antenna E-Field, Current distribution and radiation patterns have been analyzed using CST microwave studio in this article.